Classroom Assessment Practice in Mathematics Subjects for Students with Special Education Needs - Muslim, Muhammad Ashraaf Bin; Yasin, Mohd Hanafi Mohd (Angstrom Centre of Education, 2023)
The study aims to identify the practice of Classroom Assessment (PBD) practiced by Special Education teachers, especially Pupils with Special Educational Needs for Learning Problems (MBPK). The researcher used a qualitative method for this study. The study participants consisted of three Special Education teachers who taught Mathematics in Gombak district. They were selected using a purposive sampling method. All study participants were interviewed using a semi-structured instrument adapted from several other studies. The research data collected was analyzed thematically. A total of three themes have been established which are drilling methods, role playing and small games. The findings of the study show that all three teachers use written exercises in the form of handing out worksheets at the end of each teaching and learning session. While for the small game method, the research findings show that only two teachers apply this method. As for the role playing method, only one out of three teachers uses this method. Overall, it can be concluded that the study participants have used various methods when performing classroom assessment. Therefore, special education teachers need to equip themselves with a variety of knowledge and skills in carrying out classroom assessments so that MBPK can assess their true level of intelligence.